Islamic Science, Literacy and Education: Qur'anic Study of Surah Al-Alaq Verses 1 to 6 - Nur Jamilah; Sarwadi Sulisno (Konsultan Jurnal Ilmiah Indonesia, 2025)
Knowledge and literacy play a very important role in the development of education and Islamic civilization. This is reflected in the first revelation received by the Prophet Muhammad, namely Surah Al-‘Alaq verses 1–6, which emphasize the urgency of reading, learning, and the acquisition of knowledge as the primary foundation of Islamic education. This study aims to analyze the concept of knowledge and literacy from the Qur’anic perspective through an examination of Surah Al-‘Alaq verses 1–6 and their relevance to Islamic education. The method used is qualitative research with a library research approach, employing the Qur’an and authoritative books of tafsir as the main data sources, as well as scholarly books and journal articles as supporting sources. The results of the study indicate that the command iqra’ carries a broad meaning, not limited to reading written texts, but also encompassing the understanding of reality and life phenomena. This concept affirms that Islamic education should be directed toward the holistic development of students’ intellectual, spiritual, and moral dimensions. Therefore, the values of knowledge and literacy contained in Surah Al-‘Alaq verses 1–6 make an important contribution to strengthening Islamic education oriented toward the values of monotheism, scholarship, and character formation.